2017
DOI: 10.1186/s12866-017-0974-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of plant beneficial and human pathogenic bacteria isolated from salad vegetables in India

Abstract: BackgroundThe study aimed at enumerating, identifying and categorizing the endophytic cultivable bacterial community in selected salad vegetables (carrot, cucumber, tomato and onion). Vegetable samples were collected from markets of two vegetable hot spot growing areas, during two different crop harvest seasons. Crude and diluted vegetable extracts were plated and the population of endophytic bacteria was assessed based on morphologically distinguishable colonies. The bacterial isolates were identified by grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 61 publications
1
24
0
1
Order By: Relevance
“…Other major plant generated toxins may include phytohaemagglutinin, for red Kidney beans, solanines, for tomato and potato, and for oxalates (spinach and rhubarb) (20)(21)(22). Although washing can be applied to remove these contaminant, in order to further ensure the complete removal of the toxins, the regulatory o bodies like the Center for Disease Control and Prevention (CDC), US Food and Drug Administration (FDA), World Health Organization (WHO) and Center for Science in the Public Interest (CSPI) need to instill the relevant monitoring programs which may include the dietary studies focused to maintain safe and tolerable levels of the natural contaminants (14,23,24).…”
Section: Vegetables and Food Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Other major plant generated toxins may include phytohaemagglutinin, for red Kidney beans, solanines, for tomato and potato, and for oxalates (spinach and rhubarb) (20)(21)(22). Although washing can be applied to remove these contaminant, in order to further ensure the complete removal of the toxins, the regulatory o bodies like the Center for Disease Control and Prevention (CDC), US Food and Drug Administration (FDA), World Health Organization (WHO) and Center for Science in the Public Interest (CSPI) need to instill the relevant monitoring programs which may include the dietary studies focused to maintain safe and tolerable levels of the natural contaminants (14,23,24).…”
Section: Vegetables and Food Safetymentioning
confidence: 99%
“…The prevalence of the endophytic cultivable bacterial community like Salmonella spp., Escherichia coli, Bacillus cereus, Campylobacter spp., Yersinia enterocolitica, Listeria monocytogenes, Clostridium botulinum, yeasts, molds, some viruses and parasites in the salad vegetables like carrots, cucumbers, tomatoes or onions are not unlikely (22,(25)(26)(27). The incidents of Listeriosis, the E. coli 0157 outbreak, and the Salmonella outbreak upon consumption of mixed salad vegetables unfortunately seem to be common (23). As mentioned in the earlier reports, besides the potential health offers from the fresh vegetables, the point of safety and the quality of vegetables is of clinical significance due to an array of disease outbreaks (23).…”
Section: Pathogenic Bacteria Associated With Vegetables and The Fatalitymentioning
confidence: 99%
“…These bacteria could adapt and persist in plant environment and increase the chance of transmitting to humans via consumption of plants or plant-derived products. Nithya and Babu [23] reported the existence of Stenotrophomonas rhizophila, Arthrobacter mysorens, Xanthomonas axonopodis, and Aeromonas hydrophila that were not encountered in this study. The findings of this study also differ from the results of Kemajou et al [26] who reported Escherichia coli as the predominant (29.3%) and which was followed by Staphylococcus aureus (22.9%).…”
Section: Discussionmentioning
confidence: 51%
“…In this part of the country, domestic sewage, industrial and municipal waste water is used for irrigating vegetable crops. This could be responsible for the presence of human pathogenic bacterial load observed in salad vegetables, in addition to contamination through human and farm animal waste in agricultural lands, postharvest handling, transport, storage and poor hygiene conditions prevailing in market places [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation